Design and Evaluation of a Secure QR Code–Based Android Attendance System for Vocational Schools: A Case Study at SMK Darul Fikri - Indriyani Indriyani; Linda Monika; Suyono Suyono (YHMM PUBLISHING, 2026)
The digital transformation of educational administration requires efficient and secure attendance management systems to replace conventional paper-based methods. This study aims to design, develop, and evaluate a secure Android-based student attendance application utilizing QR Code technology at SMK Darul Fikri, Indonesia. The system was developed using the Waterfall software development model, encompassing requirements analysis, system design, implementation, testing, and deployment. Functional validation was conducted through Black Box Testing, while user acceptance was evaluated using a questionnaire covering three dimensions: usability, security, and user interface. The findings demonstrate that the proposed application significantly improves attendance efficiency by reducing attendance recording time from approximately 10–15 minutes to less than two minutes per class while providing automatic attendance reports for teachers. The application achieved usability, security, and interface satisfaction scores of 92%,88%, and 95%, respectively, with an overall average score of 91.7%, indicating that the system is categorized as highly feasible for implementation. In addition, server-side QR Code validation, role-based access control, and password encryption enhance data integrity and minimize attendance fraud. The results indicate that the proposed system not only improves administrative efficiency but also provides a reliable, secure, and user-friendly digital attendance solution that supports smart school initiatives and digital transformation in vocational education.